9th Burnaby Biennial Print Show. - Burnaby Art Gallery, Burnaby (Burnaby : Burnaby Art Gallery, 1977)
Weber, Kay Murray ; Andrew, David ; Brannen, Alison ; Helfield, Tilya ; Hess, Paul ; Heywood, J.C. ; Kakegamic, Josh ; Kemble, Diana ; Marois, Laureat ; McCall, Ann ; Schmidt, Marianna ; Tousignant, Serge ; Allen, George ; Armstrong, A.E. ; Barry, A. Meredith ; Bassett, Theresa ; Bell, Carol ; Benedict, Irmgard ; Bercovitch, Myrna ; Black, Sam ; Blackwood, David ; Brodie, Jim ; Caiserman-Roth, Ghitta ; Caldwell, Diana ; Cave, Jim ; Clement, George S. ; Cohen, Sorel ; Davison, Betty ; Dickson, Jennifer ; Drum, Sydney ; Eastcott, R. Wayne ; Eckert, Ron ; Esler, John K. ; Finn, Christopher ; Forrest, Elizabeth ; Game, Robert ; Gardiner, Leonard ; Gersovitz, Sarah Valerie ; Greer, John ; Haeseker, Alexandra ; Hannah, Lucie ; Hayano, K. ; Howorth, E.J. ; Klayman, Al ; Kyba, A. ; Lapointe, Frank ; Lax, Tomas ; Lobchuk, Bill ; Low, June ; Martin, Alan ; Metcalfe, Eric W. ; Morrissey-Clayton, M. ; Myers, Edna ; Olson, Gary ; Onley, Toni ; Paton, David ; Patterson, Calyton ; Peters, Barry ; Porter, Edward ; Plear, Scott ; Rawlyck, Mary E. ; Reid, Leslie ; Reynolds, David ; Rutherford, Erica ; Schwarz, Judith ; Sheckter, Bonnie ; Shiner, Jerry ; Simons, L. ; Smith, Irene ; Sopher, Shelly ; Stogre, P.A.Z. ; Swartzman, Roslyn ; Tahedle, Ernestine ; Yates, Richard ; Zeigler-Sungur, Barbara ; Zurosky, Louise
9th burnaby biennial print show, Burnaby Art Gallery, Burnaby, october 12 - november 20, 1977
boek